MENURUNKAN LEADTIME PADA PROSES REMOVE AND INSTALL TIRE FORKLIFT DIESEL KOMATSU 3 - 5 TON DENGAN ALAT BANTU WHEEL JACK HIDRAULIC DI PT. XYZ - Abikusna, Setia Abikusna (Dinamika : Jurnal Ilmiah Teknik Mesin, 2023)
XYZ's unit sales in the 2022 period reached 651 units from all sectors. Overall sales of PT. XYZ was dominated by sales of 247 units of Komatsu Forklift products. In the process of removing and installing tires for Komatsu forklifts, there is a problem of a high lead time for removing and installing tires, which is 50 minutes, not according to the task list (Standard) of 40 minutes, due to the absence of assistive devices and heavy tire loads reaching 60 kg. To solve this problem, the DMAIC method is used. Improvements made by a tool called the Hydraulic Wheel Jack and SOP for how to use the tool This tool can reduce non-standard lead time, increase as much as 88% in the ease of removal and installation, increase 96% safety for mechanics, and increase 100% morale for mechanics.